Methods and technologies of automation of technical training of manufacture of the industrial enterprises - Бабак, В.П.; Павленко, П.М.; Руденко, П.О. (Proceedings of National Aviation University (archive), 2004)
The analysis of methods of automation of technical training of manufacture based on modern information technologies is carried out. The approaches to the decision of problems of technical training of manufacture are offered